Method for preparing (NH4) 4Mo8O26 powder
Through the one-step hydrothermal method, using raw materials such as ammonium molybdate, the existing ammonium octamolybdate preparation problem is solved, and the preparation of high purity and uniform morphology is achieved, which simplifies the process flow and improves the quality of the product.
Patent Information
- Application Number
- CN202411668937.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-04-11
AI Technical Summary
There are problems such as difficult material preparation, low purity, and complicated steps during the preparation process of ammonium octamolybdate ((NH4)4Mo8O26).
The reaction process was controlled by using a one-step hydrothermal method, ammonium molybdate, lithium fluoride, analytical pure acetic acid, urea and deionized water as raw materials. By accurately adjusting the reaction conditions and additive ratio, the reaction process was controlled to produce high-purity (NH4)4Mo8O26 powder.
The preparation of (NH4)4Mo8O26 powder with high purity, impurities and uniform morphology is achieved, the process flow is simplified, the preparation temperature is reduced, and the purity and morphology of the product are improved.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic chemical powder synthesis methods, and specifically relates to a method for preparing ammonium octamolybdate powder based on a one-step hydrothermal method. Background Art
[0002] Ammonium octamolybdate ((NH4)4Mo8O 26 ) belongs to the P-1 space group and belongs to the triclinic system. The specific lattice parameters are a=10.595 Å, b=10.047 Å, c=7.882 Å, α=105.66°, β=101.08°, γ=113.40°. Mo8O 26 4- The core structure of the anion is composed of an octahedral unit consisting of four molybdenum atoms, each of which is coordinated with six oxygen atoms. Among the four octahedrons, the central molybdenum atoms of three octahedrons form terminal coordination with two oxygen atoms, while the other octahedron has only one terminal oxygen atom. These octahedrons are connected to the oxygen atoms of adjacent octahedrons through their edges to form a three-dimensional network structure, whose asymmetry and coordination distortion are the remarkable characteristics of its structure.
[0003] One-dimensional (NH4)4Mo8O 26 It has attracted wide attention due to its outstanding catalytic performance, especially in the olefin epoxidation reaction, when tert-butyl hydroperoxide (TBHP) or hydrogen peroxide (H2O2) is used as the oxidant, this catalyst shows excellent activity and stability. 26 It has shown significant potential as an additive for polyvinyl chloride (PVC) plastics. It effectively improves the flame retardant properties of the material and significantly reduces the generation of smoke by catalyzing the oxidation of carbon particles in PVC plastics. This application not only enhances the safety of PVC plastic products in the event of fire and reduces the risk of fire. It also opens up a new direction for the research and development of efficient and environmentally friendly flame retardant materials. However, regarding (NH4)4Mo8O 26 There are very few studies on the synthesis of (NH4)4Mo8O in the paper "A one-dimensional polyoxomolybdate polymer as catalyst for the epoxidation of olefins". M. Najafi et al. used a hydrothermal method to successfully synthesize (NH4)4Mo8O using ammonium molybdate, zinc chloride, phthalic acid and concentrated hydrochloric acid as raw materials. 26Powder. TA Borukaev et al. prepared (NH4)4Mo8O by solution synthesis in the paper "Improving the fire resistance of PVC plastic: the introduction of ammoniumoctamolybdate". 26 Powder. During the experiment, ammonium molybdate was first dissolved in distilled water and heated to 90-95°C. Then, a MoO3 aqueous suspension was added. Stirring was continued at this temperature for 3-5 hours until MoO3 was completely dissolved, and then the volume of the solution was reduced by a rotary evaporator. It was allowed to stand at room temperature and filtered after white crystals precipitated. Finally, the crystals were washed with deionized water and dried in a vacuum oven at 70°C to constant weight, and (NH4)4Mo8O 26 Powder.
[0004] In addition, (NH4)4Mo8O 26 It can also be used to prepare Mo4O 11 In the field of electrochemical energy, micron-sized Mo4O 11 The material exhibits excellent cycle stability and high rate performance in battery electrode applications. For example, Duan et al. 11 To improve excellent cycle stability of MoO2 nanoparticles for lithium-ion battery" found that at a current density of 100 mA g -1 In the test of 100 cycles under the condition of 11 The composite material was able to hold 400mAh g -1 This performance is significantly better than that of the single-phase MoO2 electrode material, which has a capacity of only 300 mAh g under the same test conditions. -1 This result shows that the introduction of Mo4O 11 , which not only increases the reversible capacity of MoO2 electrode materials, but also significantly improves their performance stability during long-term cyclic use. 11 -anchored ultralight graphene for high-energy lithium sulfur batteries" Found in: Mo4O 11The nanoparticles not only have a strong adsorption capacity for lithium polysulfide, but also have a high Coulomb efficiency (96%). At the same time, the introduction of Mo4O 11 The above research results show that Mo4O 11 It is a highly potential battery negative electrode material with high capacity and high cycle stability. 11 The methods are mainly limited to solid phase synthesis. For example, Vincent et al. 11 "Ammonium molybdate was used as a precursor and was preliminarily calcined in a box at about 750°C for 10 to 12 hours. The ground product was calcined again at about 750°C for 10 to 12 hours. The obtained MoO3 powder was mixed with molybdenum (Mo) metal powder in a mass ratio of 15:1, and the mixture was pressed into a sheet with a diameter of about 6 mm and sealed in a vacuum silica bottle, and then heated to 800°C in a box furnace for 2 hours. The bottle was quickly quenched in room temperature water to finally obtain Mo4O 11 Although this method is effective, it involves multiple calcination and vacuum heat treatment steps, and the process is complicated. Studies have shown that (NH4)4Mo8O 26 It can be used as a precursor and converted into Mo4O by heating and pyrolysis. 11 Wienold et al. reported in the paper “Insight in the thermal decomposition of ammonium heptamolybdate” that (NH4)4Mo8O 26 When heated to about 350℃, the amorphous phase Mo4O begins to form. 11 , the heating temperature was increased to 450 °C to obtain crystallized Mo4O 11 Therefore, by heating and cracking (NH4)4Mo8O 26 Precursors that can simplify Mo4O 11 The powder preparation process not only reduces the preparation temperature but also improves the product purity.
[0005] In summary, the present invention prepares high-purity, impurity-free and uniformly morphological (NH4)4Mo8O by hydrothermal method. 26 The powder has opened up new research paths for multiple application fields such as catalysts, additives for PVC plastics, and precursors for molybdenum-based oxide powders. The preparation method of the invention is simple, the raw materials are easily available, and the cycle is short, and it has wide practical application potential. Summary of the invention
[0006] The present invention aims to solve the problem of ammonium octamolybdate ((NH4)4Mo8O 26 ) Difficulties encountered in the preparation process, such as difficulty in material preparation, low purity, and complicated steps. Provided is a hydrothermal method for preparing (NH4)4Mo8O 26 The new process for preparing powders has a technical solution of using ammonium molybdate, lithium fluoride, analytical grade acetic acid, urea and deionized water as raw materials. The specific operation steps include: (1) preparing ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and lithium fluoride (LiF) 1:(0~3.5) molar ratio, accurately weigh and place in a beaker. (2) Add ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and acetic acid in a molar volume ratio of 1 mol: (10~15) L; and gradually add it dropwise to the beaker in step (1), and use magnetic stirring to mix the solution evenly. (3) According to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and urea in a molar ratio of 1: (2~4), accurately weigh urea; add it to the solution of step (2) and stir until it is completely dissolved. (4) Deionized water is measured according to the volume ratio of acetic acid to deionized water of 1: (0~1), and added to the solution of step (3). (5) The solution of step (4) is transferred to the lining of a hydrothermal kettle and sealed, and then the hydrothermal kettle is transferred to an oven and heated at 160 to 200°C and maintained for 6 to 48 hours. (6) After the hydrothermal reaction is completed, the hydrothermal kettle is removed and allowed to cool naturally to room temperature, the solid phase product is separated by centrifugation, and the product is washed with deionized water; this process is repeated until the pH value of the solution is about 7. Finally, the washed sample is placed in an oven and dried at 60°C to obtain the final (NH4)4Mo8O 26 ) powder. Principle of the Invention
[0007] The present invention is based on ammonium molybdate ((NH4)6Mo7O 24 4H2O) ionizes MoO4 in acidic solution 2- The core working principle involves using acetic acid to adjust the pH of the solution, forming an unstable molybdenum acetate complex during the hydrothermal reaction to control the hydrolysis of Mo ions and promote the reaction with urea to finally form ammonium octamolybdate ((NH4)4Mo8O 26 ) powder.
[0008] Specifically, MoO4 2- The ions react with acetic acid to form unstable molybdenum acetate complexes. This process effectively hinders the direct hydrolysis of molybdenum ions and enables precise control of the product formation process. The reaction equation is as follows:
[0009] MoO42- (l) +2CH3COOH (l) =[(CH3COO)2MoO3] 2- (l) +H2O (l) (1)
[0010] During the hydrothermal synthesis, the molybdenum acetate complex [(CH3COO)2MoO3] 2- Reacts with urea and water to form (NH4)4Mo8O 26 Precipitation and release of CO2 gas, as shown in equation (2):
[0011] 8[(CH3COO)2MoO3] 2- (l) +2CO(NH2) 2(s) +4H2O (l) =(NH4)4Mo8O 26(s) +16CH3COO - (l) +2CO 2(g) (2)
[0012] Where l represents liquid, s represents solid and g represents gas. In this process, the initially formed (NH4)4Mo8O 26 The nanoparticles acted as nucleation sites and subsequently formed rod-shaped (NH4)4Mo8O 26 Material.
[0013] (NH4)4Mo8O prepared by the present invention 26 The material not only has high purity and uniform morphology, but also has a simple preparation method, readily available raw materials, and a short reaction cycle. 26 ) powder has shown wide application potential in the fields of catalysis, PVC material additives, etc., and is also a good choice for preparing Mo4O 11 High-quality precursors of nanomaterials. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The bulk (NH4)4Mo8O prepared in Example 1 26 XRD spectra of the materials.
[0015] Figure 2 The bulk (NH4)4Mo8O prepared in Example 1 26 SEM images of the materials.
[0016] Figure 3 The bulk (NH4)4Mo8O prepared in Example 1 26EDS spectra of the materials.
[0017] Figure 4 The rod-shaped (NH4)4Mo8O prepared in Example 2 26 XRD spectra of the materials.
[0018] Figure 5 The rod-shaped (NH4)4Mo8O prepared in Example 2 26 SEM images of the materials.
[0019] Figure 6 The rod-shaped (NH4)4Mo8O prepared in Example 3 26 XRD spectra of the materials.
[0020] Figure 7 The bulk (NH4)4Mo8O prepared in Example 3 26 SEM images of the materials.
[0021] Figure 8 The rod-shaped (NH4)4Mo8O prepared in Example 4 26 XRD spectra of the materials.
[0022] Fig. 9 The rod-shaped (NH4)4Mo8O prepared in Example 4 26 SEM images of the materials.
[0023] Fig.10 It is (NH4)4Mo8O prepared in Example 5 26 XRD spectrum of powder.
[0024] Fig.11 The bulk (NH4)4Mo8O prepared in Example 6 26 XRD spectra of the materials.
[0025] Fig.12 The bulk (NH4)4Mo8O prepared in Example 6 26 SEM images of the materials.
[0026] Fig.13 The bulk (NH4)4Mo8O prepared in Example 6 26 EDS spectra of the materials.
[0027] Fig.14 The rod-shaped (NH4)4Mo8O prepared in Example 7 26 XRD spectra of the materials.
[0028] Fig.15 The rod-shaped (NH4)4Mo8O prepared in Example 8 26 XRD spectra of the materials.
[0029] Fig.16 The rod-shaped (NH4)4Mo8O prepared in Example 8 26 SEM images of the materials.
[0030] Fig.17 The rod-shaped (NH4)4Mo8O prepared in Example 9 26 XRD spectra of the materials.
[0031] Embodiment 1:
[0032] Ammonium molybdate, analytical grade acetic acid, urea and deionized water are used as raw materials. The specific steps are as follows: (1) According to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and acetic acid in a molar volume ratio of 1 mol:14L; and the two were placed in a beaker and the solution was mixed evenly by magnetic stirring; (2) ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and urea in a molar ratio of 1:3.5; add it to the solution of step (1) and stir until it is completely dissolved. (3) Deionized water is measured according to the volume ratio of acetic acid to deionized water of 1:0.75; and add it to the solution of step (2). (4) The solution of step (3) is transferred to the inner lining of the hydrothermal kettle (filling degree is about 70%), sealed and placed in an oven. The heating temperature is set to 160°C and kept warm for 24 hours. (5) After the reaction is completed, take out the hydrothermal kettle and cool it naturally to room temperature. Centrifuge to separate the solid phase product and wash the product with deionized water; repeat several times until the pH of the supernatant is about 7. The centrifuged sample is placed in an oven and dried at 60°C to obtain (NH4)4Mo8O 26 Powder.
[0033] The prepared (NH4)4Mo8O 26 The powder was subjected to X-ray diffraction phase analysis (XRD), and the results were as follows Figure 1 Its main diffraction peaks are all related to (NH4)4Mo8O 26 The three strong diffraction peaks are located at 12.26°, 27.76°, and 30.27°, corresponding to the triclinic (NH4)4Mo8O 26 The (0-11), (2-20) and (211) crystal planes of the phase.
[0034] Figure 2 The prepared (NH4)4Mo8O 26 Scanning electron microscope (SEM) image of the material. The material has a block structure with a length of 2-10μm and a width of about 2μm (e.g. Figure 2(as shown in (a)). Figure 2 (b) shows that the bulk (NH4)4Mo8O 26 The material has an angular structure and a relatively smooth, dense surface. Further analysis by energy dispersive spectrometry (EDS) yields the following EDS spectra: Figure 3 As shown. The spectrum shows the characteristic peaks of three elements: N, O and Mo. Combined with the XRD spectrum results, it is confirmed that the product is (NH4)4Mo8O 26 Mutually.
[0035] Embodiment 2:
[0036] Ammonium molybdate, analytical grade acetic acid, urea and deionized water are used as raw materials. The specific steps are as follows: (1) According to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and acetic acid in a molar volume ratio of 1 mol:14L ammonium molybdate and acetic acid were weighed; the two were placed in a beaker and the solution was mixed evenly by magnetic stirring; (2) according to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and urea in a molar ratio of 1:3.5; add it to the solution of step (1) and stir until it is completely dissolved; (3) measure deionized water according to the volume ratio of acetic acid to deionized water of 1:0.75; add it to the solution of step (2); (4) transfer the solution of step (3) to the lining of the hydrothermal kettle (filling degree is about 70%), seal it and transfer the hydrothermal kettle to the oven; set the heating temperature to 160℃ and keep it warm for 12 hours. (5) After the reaction is completed, take out the hydrothermal kettle and cool it naturally to room temperature. Centrifuge to separate the solid phase product and wash the product with deionized water; repeat several times until the pH of the supernatant is about 7. The centrifuged sample is placed in an oven and dried at 60℃ to obtain (NH4)4Mo8O 26 Powder.
[0037] The prepared (NH4)4Mo8O 26 The powder was subjected to X-ray diffraction phase analysis (XRD), and its XRD spectrum was as follows Figure 4 Its main characteristic diffraction peaks are all related to (NH4)4Mo8O 26 The diffraction peaks of the three strong diffraction peaks are located at 12.26°, 24.71° and 30.27°, which correspond to the triclinic (NH4)4Mo8O 26 The (0-11), (-211) and (211) crystal planes of the prepared (NH4)4Mo8O 26 The material is single phase and high purity.
[0038] Figure 5The prepared (NH4)4Mo8O 26 Scanning electron microscope (SEM) image of the material. The results show that the material has a rod-like structure with a length of 5-30μm and a width of about 2μm (e.g. Figure 5 (as shown in (a)). Figure 5 (b) shows that the rod-shaped (NH4)4Mo8O 26 The material has an angular structure and a relatively smooth, dense surface.
[0039] Embodiment 3:
[0040] Ammonium molybdate, analytical grade acetic acid, urea and deionized water are used as raw materials. The specific steps are as follows: (1) According to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and acetic acid in a molar volume ratio of 1 mol:14L ammonium molybdate and acetic acid were weighed; the two were placed in a beaker and the solution was mixed evenly by magnetic stirring; (2) according to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and urea in a molar ratio of 1:3.5; add it to the solution of step (1) and stir until it is completely dissolved; (3) measure deionized water according to the volume ratio of acetic acid to deionized water of 1:0.75; add it to the solution of step (2); (4) transfer the solution of step (3) to the inner lining of the hydrothermal kettle (filling degree is 70%), seal it and transfer the hydrothermal kettle to the oven, set the heating temperature to 180℃ and keep it warm for 24 hours. (5) After the reaction is completed, take out the hydrothermal kettle and cool it naturally to room temperature, centrifuge to separate the solid phase product, and wash the product with deionized water; repeat several times until the pH of the supernatant is about 7, place the clean sample by centrifugation in an oven, and dry it at 60℃ to obtain (NH4)4Mo8O 26 Powder.
[0041] The prepared (NH4)4Mo8O 26 The powder was subjected to X-ray diffraction phase analysis (XRD), and the obtained XRD spectrum was as follows Figure 6 Its main characteristic diffraction peaks are all related to (NH4)4Mo8O 26 The diffraction peaks of the three strong diffraction peaks are located at 12.26°, 30.27° and 24.71°, which correspond to the triclinic (NH4)4Mo8O 26 phase (0-11), (211) and (-211) crystal planes; this indicates that the prepared (NH4)4Mo8O 26 The material is single-phase, high-purity, and almost free of other crystalline impurity phases.
[0042] Figure 7Prepared (NH4)4Mo8O 26 Scanning electron microscope (SEM) image of the material. The results show that the prepared (NH4)4Mo8O 26 The material has a rod-like structure with a length of 5-20 μm and a width of about 2-3 μm (e.g. Figure 7 (as shown in (a)). Figure 7 (b) shows that the rod-shaped (NH4)4Mo8O 26 The angular structure of the material is no longer obvious, and the surface is relatively smooth and dense.
[0043] Embodiment 4:
[0044] Ammonium molybdate, analytical grade acetic acid, urea and deionized water are used as raw materials. The specific steps are as follows: (1) According to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and acetic acid in a molar volume ratio of 1 mol:14L ammonium molybdate and acetic acid were weighed; the two were placed in a beaker and the solution was mixed evenly by magnetic stirring; (2) according to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and urea in a molar ratio of 1:3.5; add it to the solution of step (1) and stir until it is completely dissolved; (3) take deionized water according to the volume ratio of acetic acid to deionized water of 1:0.75; add it to the solution of step (2); (4) transfer the solution of step (3) to the lining of the hydrothermal kettle (filling degree is about 70%). Seal and transfer the hydrothermal kettle to an oven, set the heating temperature to 200℃ and keep it warm for 24 hours. (5) After the reaction is completed, take out the hydrothermal kettle, cool it naturally to room temperature, centrifuge to separate the solid phase product, and wash the product with deionized water, repeat several times; until the pH of the supernatant is about 7, the sample after centrifugation is placed in an oven and dried at 60℃ to obtain (NH4)4Mo8O 26 Powder.
[0045] The prepared (NH4)4Mo8O 26 The powder was subjected to X-ray diffraction phase analysis (XRD), and the results were as follows Figure 8 Its main characteristic diffraction peaks are all related to (NH4)4Mo8O 26 The diffraction peaks of the three strong diffraction peaks are located at 12.26°, 30.27° and 27.76°, which correspond to the triclinic (NH4)4Mo8O 26 phase (0-11), (211) and (2-20) crystal planes; this indicates that the prepared (NH4)4Mo8O 26 The material is single-phase, high-purity, and almost free of other crystalline impurity phases.
[0046] Fig. 9 Prepared (NH4)4Mo8O 26 Scanning electron microscope (SEM) images of the material. The results show that the material has a rod-like structure with a length of 8-38μm and a width of 3-7μm (e.g. Fig. 9 (as shown in (a)). Fig. 9 (b) shows that the rod-shaped (NH4)4Mo8O 26 The material has an angular structure and a relatively smooth and dense surface.
[0047] Embodiment 5:
[0048] Ammonium molybdate, lithium fluoride, analytical grade acetic acid and urea are used as raw materials. The specific steps are as follows: (1) Prepare ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and lithium fluoride (LiF) were weighed in a molar ratio of 1:3.5 and transferred to a beaker; (2) ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and acetic acid in a molar volume ratio of 1 mol:14L; gradually add it dropwise to the beaker mentioned in (1), and mix the solution evenly by magnetic stirring; (3) according to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and urea in a molar ratio of 1:3.5; add it to the solution of step (2) and stir until it is completely dissolved; (4) transfer the solution of step (3) to the inner lining of the hydrothermal kettle and seal it (the filling degree is about 40%); transfer the hydrothermal kettle to an oven, set the heating temperature to 180°C and keep it warm for 12 hours. (5) After the reaction is completed, take out the hydrothermal kettle, cool it to room temperature, centrifuge to separate the solid phase product, wash the product with deionized water, and repeat several times; until the pH of the supernatant is about 7. The centrifuged sample is placed in an oven and dried at 60°C to obtain (NH4)4Mo8O 26 Powder.
[0049] The prepared (NH4)4Mo8O 26 The powder was subjected to X-ray diffraction phase analysis (XRD), and the obtained XRD spectrum was as follows Fig.10 Its main characteristic diffraction peaks are all related to (NH4)4Mo8O 26 The three strong diffraction peaks are located at 12.26°, 24.71° and 30.27°, corresponding to the triclinic (NH4)4Mo8O 26 phase (0-11), (-211) and (211) crystal planes; this indicates that the prepared (NH4)4Mo8O 26 The material is single phase and of high purity.
[0050] Embodiment 6:
[0051] Ammonium molybdate, lithium fluoride, analytical grade acetic acid, urea and deionized water are used as raw materials. The specific steps are as follows: (1) According to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and lithium fluoride (LiF) were weighed in a molar ratio of 1:3.5 and transferred to a beaker; (2) ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and acetic acid in a molar volume ratio of 1 mol:14L; gradually add it dropwise to the beaker mentioned in (1), and mix the solution evenly by magnetic stirring; (3) according to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and urea in a molar ratio of 1:3.5; add it to the solution of step (2) and stir until it is completely dissolved; (4) take deionized water according to the volume ratio of acetic acid to deionized water of 1:0.75; add it to the solution of step (3); (5) transfer the solution of step (4) to the inner lining of the hydrothermal kettle and seal it (the filling degree is about 70%); transfer the hydrothermal kettle to an oven, set the heating temperature to 180°C and keep it warm for 12 hours. (6) After the reaction is completed, take out the hydrothermal kettle, cool it naturally to room temperature, centrifuge to separate the solid phase product, and wash the product with deionized water, repeat several times until the pH of the supernatant is about 7. The centrifuged sample is placed in an oven and dried at 60°C to obtain (NH4)4Mo8O 26 Powder.
[0052] The prepared (NH4)4Mo8O 26 The powder was subjected to X-ray diffraction phase analysis (XRD), and the obtained XRD spectrum was as follows Fig.11 Its main characteristic diffraction peaks are all related to (NH4)4Mo8O 26 The three strong diffraction peaks are located at 12.26°, 30.27°, and 37.60°, corresponding to the triclinic (NH4)4Mo8O 26 phase (0-11), (211) and (3-20) crystal planes; this indicates that the prepared (NH4)4Mo8O 26 The material is single phase and of high purity.
[0053] Fig.12 Prepared (NH4)4Mo8O 26 Scanning electron microscope (SEM) images of the material. The results show that the material has a block structure with a length of 8-70μm and a width of about 8μm (e.g. Fig.12 (as shown in (a)). Fig.12 (b) shows that the bulk (NH4)4Mo8O 26The material has an angular structure and a relatively smooth and dense surface. 26 The powder was subjected to EDS point analysis, and the obtained spectrum was as follows Fig.13 The spectrum contains four elements: N, O, F, and Mo. Combined with the XRD spectrum, it can be seen that the prepared product is (NH4)4Mo8O 26 Mutually.
[0054] Ammonium molybdate, lithium fluoride, analytical grade acetic acid, urea and deionized water are used as raw materials. The specific steps are as follows: (1) ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and lithium fluoride (LiF) were weighed in a molar ratio of 1:3.5 and transferred to a beaker; (2) ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and acetic acid in a molar volume ratio of 1 mol:14L; gradually add it dropwise to the beaker mentioned in (1), and mix the solution evenly by magnetic stirring; (3) according to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and urea in a molar ratio of 1:3.5; add it to the solution of step (2) and stir until completely dissolved; (4) measure deionized water according to the volume ratio of acetic acid to deionized water of 1:0.75; add it to the solution of step (3); (5) transfer the solution of step (4) to the inner lining of the hydrothermal kettle and seal it (the filling degree is about 70%). Transfer the hydrothermal kettle to an oven, set the heating temperature to 180°C and keep it warm for 6 hours. (6) After the reaction is completed, take out the hydrothermal kettle, cool it naturally to room temperature, centrifuge to separate the solid phase product, and wash the product with deionized water, repeat several times until the pH of the supernatant is about 7. The centrifuged sample is placed in an oven and dried at 60°C to obtain (NH4)4Mo8O 26 Powder.
[0055] The prepared (NH4)4Mo8O 26 The powder was subjected to X-ray diffraction phase analysis (XRD), and the obtained XRD spectrum was as follows Fig.14 Its main characteristic diffraction peaks are all related to (NH4)4Mo8O 26 The three strong diffraction peaks are located at 12.26°, 24.71° and 30.27°, corresponding to the triclinic (NH4)4Mo8O 26 phase (0-11), (-211) and (211) crystal planes; this indicates that the prepared (NH4)4Mo8O 26 The material is single phase and of high purity.
[0056] Embodiment 8:
[0057] Ammonium molybdate, lithium fluoride, analytical grade acetic acid, urea and deionized water are used as raw materials. The specific steps are as follows: (1) ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and lithium fluoride (LiF) were weighed in a molar ratio of 1:3.5 and transferred to a beaker; (2) ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and acetic acid in a molar volume ratio of 1 mol:14L; gradually add it dropwise to the beaker mentioned in (1), and mix the solution evenly by magnetic stirring; (3) according to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and urea in a molar ratio of 1:3.5; add it to the solution of step (2) and stir until completely dissolved; (4) measure deionized water according to the volume ratio of acetic acid to deionized water of 1:0.75; add it to the solution of step (3); (5) transfer the solution of step (4) to the inner lining of the hydrothermal kettle and seal it (the filling degree is about 70%). Transfer the hydrothermal kettle to an oven, set the heating temperature to 180°C and keep it warm for 24 hours. (6) After the reaction is completed, take out the hydrothermal kettle, cool it naturally to room temperature, centrifuge to separate the solid phase product, wash the product with deionized water, and repeat several times until the pH of the supernatant is about 7. The centrifuged sample is placed in an oven and dried at 60°C to obtain (NH4)4Mo8O 26 Powder.
[0058] The prepared (NH4)4Mo8O 26 The powder was subjected to X-ray diffraction phase analysis (XRD), and the obtained XRD spectrum was as follows Fig.15 Its main characteristic diffraction peaks are all related to (NH4)4Mo8O 26 The three strongest diffraction peaks are located at 12.26°, 24.71°, and 30.27°, corresponding to the triclinic (NH4)4Mo8O 26 phase (0-11), (-211) and (211) crystal planes; this indicates that the prepared (NH4)4Mo8O 26 The material is single phase and high purity.
[0059] Fig.16 Prepared (NH4)4Mo8O 26 Scanning electron microscope (SEM) images of the material. The results show that the material has a block structure with a length of 6-17μm and a width of about 2μm (e.g. Fig.16 (as shown in (a)). Fig.16 (b) shows that the bulk (NH4)4Mo8O 26 The material has an angular structure and a relatively smooth and dense surface.
[0060] Embodiment 9:
[0061] Ammonium molybdate, lithium fluoride, analytical grade acetic acid, urea and deionized water are used as raw materials. The specific steps are as follows: (1) ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and lithium fluoride (LiF) were weighed in a molar ratio of 1:3.5 and transferred to a beaker; (2) ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and acetic acid in a molar volume ratio of 1 mol:14L; gradually add it dropwise to the beaker mentioned in (1), and mix the solution evenly by magnetic stirring; (3) according to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and urea in a molar ratio of 1:3.5; add it to the solution of step (2) and stir until it is completely dissolved; (4) measure deionized water according to the volume ratio of acetic acid to deionized water of 1:0.75; add it to the solution of step (3); (5) transfer the solution of step (4) to the inner lining of the hydrothermal kettle and seal it (the filling degree is about 70%). Transfer the hydrothermal kettle to an oven, set the heating temperature to 180°C and keep it warm for 48 hours. (6) After the reaction is completed, take out the hydrothermal kettle, cool it naturally to room temperature, centrifuge to separate the solid phase product, wash the product with deionized water, and repeat several times until the pH of the supernatant is about 7. The centrifuged sample is placed in an oven and dried at 60°C to obtain (NH4)4Mo8O 26 Powder.
[0062] The prepared (NH4)4Mo8O 26 The powder was subjected to X-ray diffraction phase analysis (XRD), and the obtained XRD spectrum was as follows Fig.17 Its main characteristic diffraction peaks are all related to (NH4)4Mo8O 26 The three strongest diffraction peaks are located at 12.26°, 24.71° and 30.27°, corresponding to the triclinic (NH4)4Mo8O 26 phase (0-11), (-211) and (211) crystal planes; this indicates that the prepared (NH4)4Mo8O 26 The material is single phase and of high purity.
[0063] Embodiment 10:
[0064] Ammonium molybdate, lithium fluoride, analytical grade acetic acid, urea and deionized water are used as raw materials. The specific steps are as follows: (1) ammonium molybdate ((NH4)6Mo7O 24·4H2O) and lithium fluoride (LiF) were weighed in a molar ratio of 1:1 and transferred to a beaker; (2) ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and acetic acid in a molar volume ratio of 1 mol: 15 L; and gradually add it dropwise to the beaker mentioned in (1), and use magnetic stirring to mix the solution evenly; (3) according to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and urea in a molar ratio of 1: 2; add it to the solution of step (2) and stir until it is completely dissolved; (4) take deionized water according to the volume ratio of acetic acid to deionized water of 1: 1; and add it to the solution of step (3); (5) transfer the solution of step (4) to the lining of the hydrothermal kettle and seal it; transfer the hydrothermal kettle to an oven, set the heating temperature to 160°C and keep it warm for 48 hours. (6) After the hydrothermal reaction is completed, take out the hydrothermal kettle, cool it naturally to room temperature, centrifuge to separate the solid phase product, and wash the product with deionized water, repeat several times until the pH of the supernatant is about 7. The centrifuged sample is placed in an oven and dried at 60°C to finally obtain (NH4)4Mo8O 26 Powder.
[0065] Embodiment 11:
[0066] Ammonium molybdate, analytical grade acetic acid, urea and deionized water are used as raw materials. The specific steps are as follows: (1) According to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and acetic acid in a molar volume ratio of 1 mol: 10L; accurately weigh the two and place them in a beaker, and use magnetic stirring to mix the solution evenly; (2) according to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and urea in a molar ratio of 1: 4; add it to the solution of step (1) and stir until it is completely dissolved; (3) take deionized water according to the volume ratio of acetic acid to deionized water of 1: 0.75; and add it to the solution of step (2); (4) transfer the solution of step (3) to the lining of the hydrothermal kettle and seal it; transfer the hydrothermal kettle to an oven, set the heating temperature to 200°C and keep it warm for 6 hours. (5) After the hydrothermal reaction is completed, take out the hydrothermal kettle, cool it naturally to room temperature, centrifuge to separate the solid phase product, and wash the product with deionized water, repeat several times until the pH of the supernatant is about 7. The centrifuged sample is placed in an oven and dried at 60°C to finally obtain (NH4)4Mo8O 26 Powder.
Claims
1. A method for preparing ammonium octamolybdate ((NH4)4Mo8O 26 ) A hydrothermal synthesis method of a powder, characterized in that: The method uses ammonium molybdate, lithium fluoride, analytical grade acetic acid, urea and deionized water as raw materials; and comprises the following steps: (1) preparing ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and lithium fluoride (LiF) in a molar ratio of 1:(0-3.5), accurately weigh and mix the two; (2) according to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and acetic acid in a molar volume ratio of 1 mol:(10-15) L, gradually dropwise added to the mixture obtained in step (1), and mixed evenly by magnetic stirring; (3) according to ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and urea in a molar ratio of 1:(2~4), accurately weigh urea and add it to the solution of step (2), and stir until it is completely dissolved; (4) According to the volume ratio of acetic acid to deionized water of 1:(0~1), measure deionized water and add it to the solution of step (3); (5) Transfer the solution of step (4) to the lining of the hydrothermal kettle and seal it; then place it in an oven, heat it to 160~200℃ and keep it warm for 6~48 hours; (6) After the hydrothermal reaction is completed, hydrothermal kettle, cool it naturally to room temperature, centrifuge to separate the solid phase product, and wash the product with deionized water, repeat several times until the pH of the supernatant is about 7. Then dry it in an environment of 60℃ to obtain (NH4)4Mo8O 26 Powder.